1987
DOI: 10.1159/000242656
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Beta-Endorphin Levels in Response to Reductions in Uterine Blood Flow

Abstract: Fetal β-endorphin release has been associated with fetal hypoxia. The purpose of this study was to assess the degree of uterine blood flow reduction needed to elicit fetal β-endorphin release in the sheep since there is a large reserve of oxygen supply to the fetus. Uterine blood flow was reduced by 26 ± 2, 46 ± 3 and 66 ± 2%, producing fetal oxygen content concentrations of 5.7 ± 0.6, 4.4 ± 0.7 and 2.6 ± 0.3 ml/dl, respectively. Although fetal oxygen concentrations were significantly decreased in the groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…These findings are supported by the observations of Skillman and Clark [ 14] who noted a 372% increase in circulating pendorphins (from 28.5 to 104 pmol/1) in asphyxiated fetal sheep (PO2 = 13 ± 1 Torr, pH = 7.12 ± 0.07) but only a 42% rise in animals in which pH was maintained near normal (PO2 = 14 ± 2 Torr, pH = 7.34 ± 0.01). In contrast, Wardlaw et al [15] have shown a 215% increase (from 47 to 148 pmol/1) in P-endorphin concentrations in hy poxemic fetal sheep (PO2 =11 ± 1 Torr).…”
Section: Discussionsupporting
confidence: 82%
“…These findings are supported by the observations of Skillman and Clark [ 14] who noted a 372% increase in circulating pendorphins (from 28.5 to 104 pmol/1) in asphyxiated fetal sheep (PO2 = 13 ± 1 Torr, pH = 7.12 ± 0.07) but only a 42% rise in animals in which pH was maintained near normal (PO2 = 14 ± 2 Torr, pH = 7.34 ± 0.01). In contrast, Wardlaw et al [15] have shown a 215% increase (from 47 to 148 pmol/1) in P-endorphin concentrations in hy poxemic fetal sheep (PO2 =11 ± 1 Torr).…”
Section: Discussionsupporting
confidence: 82%
“…In addition to this enhanced CNS opioid activity, several investi¬ gators have reported elevated ß-endorphin concentrations in peripheral plasma of women during parturition (Goland et al, 1981;Steinbrook et ai, 1982;Hoffman et al, 1984). Also in newborn human babies and lambs, high plasma ß-endorphin concentrations have been found, especially in conjunction with fetal distress (Wardlaw et ai, 1979;Ruth et ai, 1986;Skillman & Clark, 1987). Although the role of peripheral ß-endorphin has not yet been clarified, participation in the stress response has been postulated.…”
Section: Introductionmentioning
confidence: 99%
“…The fetus releases endorphin in response to stressful stimuli, including hypoxia [5] and reduced uterine blood flow [6]. In our study we optimized intrauterine conditions by minimizing maternal hypotension.…”
Section: Discusssionmentioning
confidence: 99%